2019
DOI: 10.3390/sym11101296
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Structural Symmetries of a U12 Engine in the Vibration Analysis of a Transmission

Abstract: The paper focuses on the vibration analysis of a vehicle equipped with two identical engines. Such solutions are encountered in practice when less power is needed for a vehicle for a certain period of time and then greater power the rest of the time. An example of this would be a mobile drilling rig. During transport (a relatively short period of time) only one engine operates and then, in service (most of the operating time), both engines operate. A characteristic of such an aggregate is the existence, within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…The monitoring method for the wear state of a tool using a convolutional bidirectional LSTM model was shown in the article [8]. The use of structural symmetries of a U12 engine using vibration analysis was presented in [9].…”
Section: The Contentmentioning
confidence: 99%
“…The monitoring method for the wear state of a tool using a convolutional bidirectional LSTM model was shown in the article [8]. The use of structural symmetries of a U12 engine using vibration analysis was presented in [9].…”
Section: The Contentmentioning
confidence: 99%
“…The main idea that helps the builder and designer is that the information needed to describe such a system is reduced, which allows a reduction of the operations required for design and calculation and to facilitate both static and dynamic analysis. Particular cases of systems with different symmetries have been studied by different authors and presented in the papers [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…For example, increasing symmetry can effectively improve the structural accuracy of compliant mechanisms, and symmetry can also affect the static and dynamic characteristics of bending mechanisms [11]. The existence of identical parts in mechanical systems leads to symmetry that allows the computations to be simplified in order to obtain suggestive and rapid results [12]. Through the transposition of the meshing point of the gear pair, it is shown that the meshing condition of the gear pair in the forward rotation and reverse rotation can be determined by the same method, that is, taking symmetry as a method to reduce the calculation [13].…”
Section: Introductionmentioning
confidence: 99%
“…Symmetry 2021, 13, x FOR PEER REVIEW 2 of 16 mechanical systems leads to symmetry that allows the computations to be simplified in order to obtain suggestive and rapid results [12]. Through the transposition of the meshing point of the gear pair, it is shown that the meshing condition of the gear pair in the forward rotation and reverse rotation can be determined by the same method, that is, taking symmetry as a method to reduce the calculation [13].…”
Section: Introductionmentioning
confidence: 99%